Photoantimicrobial and Photoantiviral Textiles: Underestimated Potential - Alexander Efimov; Serge Mordon (MDPI AG, 2024)
In this review, we summarize the present state of a rapidly developing field of light-activated antimicrobial textiles and their underestimated potential and opportunities.